Decadal Monitoring of the Hydrothermal System of Stromboli Volcano, Italy - Cinzia Federico; Salvatore Inguaggiato; Marcello Liotta; Andrea Luca Rizzo; Fabio Vita (Geochemistry, Geophysics, Geosystems, 2023)
Abstract In active volcanoes, magmatic fluids rising toward the surface may interact with shallow waters, thereby forming hydrothermal systems that record variations in magma dynamics at depth. Here, we report on a data set comprising the chemical and isotopic composition of thermal waters and dissolved gases from Stromboli Island (Aeolian Volcanic Arc, Southern Italy) that spans 14 years (2004–2018) of continuous observations. We show that the shallow thermal aquifer of Stromboli results from variable mixing between meteoric water, seawater and magmatic fluids. Gas‐water‐rock interactions occur, which induce a large spectrum of variation in both water and gas chemistry. These shallow processes do not affect the 3He/4He of helium dissolved in thermal waters, which records a magmatic signature that varies in response to changes in magma supply at depth. We show that in periods of more intense volcanic activity, the helium isotopic composition of thermal waters approaches that of the gas emitted from the magma residing at 7–10 km depth. Investigation of hydrothermal waters at active volcanoes is a promising tool to examine magmatic fluids and their shallow circulation, as well as to evaluate the state of activity of a volcano, particularly when summit areas are inaccessible.